Quantitative psychological research the complete student's companion - Clark-Carter, David (Routledge, 2024)
"Quantitative Psychological Research: The Complete Student's Companion, expertly guides the reader through all the stages involved in undertaking quantitative psychological research: designing a study, choosing a sample of people, undertaking the study, analysing the data, and reporting the research"-- Provided by publisher.